2017
DOI: 10.13057/cellbioldev/v010103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pruning on growth and yield of cucumber (Cucumis sativus) Mercy variety in The acid soil of North Kalimantan, Indonesia

Abstract: Mardhiana, Pradana AP, Adiwena M, Kartina, Santoso D, Wijaya R, Maliki A. 2017. Effects of pruning on growth and yield of cucumber (Cucumis sativus) Mercy variety in The acid soil of North Kalimantan, Indonesia. Cell Biol Dev 1: 13-17. In recent years, cucumber production in Tarakan, North Kalimantan only reaches 20 tons ha-1. In fact, cucumber production potential could reach 49 tons ha-1. Several factors that limit the low productivity of cucumbers in Tarakan are acid soil and cultivation techniques which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…According to Kabir [16], cutting apex produces the maximum amount of fruit and good quality. Similar results were revealed by [17] in tomato (Solanum esculentum L.), Slamet et al [18] in Roselle (Hibiscus sabdariffa L.), Mardhiana et al [19] in cucumber (Cucumis sativus L.), and Shilpa and Priyanka [20] in okra (Abelmoschus esculentus (L.) Moench).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…According to Kabir [16], cutting apex produces the maximum amount of fruit and good quality. Similar results were revealed by [17] in tomato (Solanum esculentum L.), Slamet et al [18] in Roselle (Hibiscus sabdariffa L.), Mardhiana et al [19] in cucumber (Cucumis sativus L.), and Shilpa and Priyanka [20] in okra (Abelmoschus esculentus (L.) Moench).…”
Section: Discussionsupporting
confidence: 85%
“…The height of the apex showed a substantial effect on the number of capsules per plant [21,22,19] indicated that the number of capsules per plant was higher in cut plants of okra. In addition, Ahmed and Oladiran [13] have shown that the apex cut increases the number of pods per plant of okra (Abelmoschus esculentus) by 10 to 40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the plant growth processes disruption caused by apex cutting. This could be also explained by the delay in plant growth (for a certain period) caused by apex cutting before the emergence of new shoots [19]. This result is in line with that of [26] Olasantan on the squash (Cucurbita maxima Duch.…”
Section: Discussionsupporting
confidence: 82%
“…Mardhiana et al, 2017). Similarly, all three fertilizer combinations (30 Mt/ ha FYM +100 % RDF of NPK, 9.4 Mt/ha vermicompost + 100% RDF of NPK and 4.3 Mt/ha Poultry manure + 100% RDF of NPK) recorded statistically similar and superior result i.e.…”
mentioning
confidence: 65%